2018
DOI: 10.1111/nep.13099
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord‐derived mesenchymal stem cells conditioned medium attenuate interstitial fibrosis and stimulate the repair of tubular epithelial cells in an irreversible model of unilateral ureteral obstruction

Abstract: This study shows that CM protects UUO-induced kidney damage and therefore could be a potential tool to prevent CKD progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…Likewise, DNA oxidation and lipid peroxidation caused by cisplatin‐induced kidney damage are alleviated by exosomes from human umbilical cord‐derived MSCs (UC‐MSCs); these results were confirmed in vitro with renal proximal tubular cells 27 . Treatments with MSCs were also demonstrated to reduce levels of ROS in animal models of diabetic retinopathy and nephropathy, severe acute pancreatitis, ureteral obstruction‐induced kidney damage, Alzheimer's disease, and metabolic renovascular disease 24,28‐32 . Specifically, MSC treatments have been shown to reduce levels of H 2 O 2 in intestinal inflammation and several organs in a model of premature aging 33,34 .…”
Section: Effect Of Mscs On Oxidative Stress Biomarkers and Rosmentioning
confidence: 89%
See 1 more Smart Citation
“…Likewise, DNA oxidation and lipid peroxidation caused by cisplatin‐induced kidney damage are alleviated by exosomes from human umbilical cord‐derived MSCs (UC‐MSCs); these results were confirmed in vitro with renal proximal tubular cells 27 . Treatments with MSCs were also demonstrated to reduce levels of ROS in animal models of diabetic retinopathy and nephropathy, severe acute pancreatitis, ureteral obstruction‐induced kidney damage, Alzheimer's disease, and metabolic renovascular disease 24,28‐32 . Specifically, MSC treatments have been shown to reduce levels of H 2 O 2 in intestinal inflammation and several organs in a model of premature aging 33,34 .…”
Section: Effect Of Mscs On Oxidative Stress Biomarkers and Rosmentioning
confidence: 89%
“…Administration of MSCs has been demonstrated to reduce levels of one or more of these markers in a variety of animal models associated with oxidative stress (Table 1). Injection of MSCs themselves may not be critical to their antioxidant effects as administration of their conditioned medium (CM) also reduced lipid peroxidation in a model of ureteral obstruction‐induced kidney injury 24 . Administration of MSC‐derived exosomes was also effective to rescue protein oxidation and lipid peroxidation in animal models of septic and hyperglycemic brain injury and cognitive impairment 25,26 .…”
Section: Effect Of Mscs On Oxidative Stress Biomarkers and Rosmentioning
confidence: 99%
“…Zhang et al [41] reported that MSC effectively reduced the level of MDA, and increased SOD in the lung tissue of acute lung injury rats. Liu et al [42] reported that MSC significantly increased the activity of glutathione (GSH), and reduced the levels of MDA in rats induced by unilateral ureteral obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [41] reported that MSC effectively reduced the level of MDA, and increased SOD in the lung tissue of acute lung injury rats. Liu et al [42] reported that MSC signi cantly increased the activity of glutathione (GSH), and reduced the levels of MDA in rats induced by unilateral ureteral obstruction.…”
Section: Discussionmentioning
confidence: 99%